Atypical MRI features in familial adult onset Alexander disease: case report. Issue 1 (December 2016) - Liu, Yonghong; Zhou, Heng; Wang, Huabing; Gong, Xiaoqing; Zhou, Anna; Zhao, Lin; Li, Xindi; Zhang, Xinghu
Abstract Background Alexander disease (AxD) is a rare neurological disease, especially in adults. It shows variable clinical and radiological features. Case presentation We diagnosed a female with AxD presenting with paroxysmal numbness of the limbs at the onset age of 28-year-old, progressing gradually to spastic paraparesis at age 30. One year later, she had ataxia, bulbar paralysis, bowel and bladder urgency. Her mother had a similar neurological symptoms and died within 2 years after onset (at the age of 47), and her maternal aunt also had similar but mild symptoms at the onset age of 54-year-old. Her brain magnetic resonance imaging (MRI) showed abnormal signals in periventricular white matter with severe atrophy in the medulla oblongata and thoracic spinal cord, and mild atrophy in cervical spinal cord, which is unusual in the adult form of AxD. She and her daughter's glial fibrillary acidic protein (GFAP) gene analysis revealed the same heterozygous missense mutation, c.1246C > T, p.R416W, despite of no neurological symptoms in her daughter. Conclusions Our case report enriches the understanding of the familial adult AxD. Genetic analysis is necessary when patients have the above mentioned symptoms and signs, MRI findings, especially with family history.